Comparison of intraocular pressure measurements between Icare PRO Tonometer, Goldmann Applanation Tonometer and non-contact tonometer in healthy and glaucomatous eyes - Queirós,Tatiana Sofia Monteiro (2018)
Abstract Purpose: To validate the comparative measurements of intraocular pressure performed with IcarePRO tonometer (IPT) in relation to Goldmann applanation tonometer (GAT) and non-contact tonometer (NCT), as well as to evaluate the influence of central corneal thickness (CCT) on these values. Methods: This was a prospective and comparative study conducted during 6 months in the Department of Ophthalmology, Hospital de Braga, Portugal. The study population comprised two groups: healthy adults and adults with primary open angle glaucoma (POAG). The IOP values were obtained by the three tonometers and the order of execution was randomly selected. CCT values were obtained by ultrasonic pachymetry. Results: A total of 168 eyes (74 with diagnosis of POAG and 94 healthy) of 84 patients were included in this study. The mean IOP values obtained by IPT, GAT and NCT were 17.36±3.78 mmHg; 14.59±3.32 mmHg; and 17.04±4.01 mmHg, respectively. The comparison between IPT and NCT did not reveal statistically significant differences in the two groups studied. However, statistically significant differences were obtained between IPT and GAT values (p <0.001). The IOP values, recorded by all the tonometers, were significantly and positivily correlated with the CCT (p <0.001). Conclusion: IOP readings measured by IPT are comparable with those obtained by NCT, but higher than those obtained by the GAT. CCT values are correlated with IOP measurements with IPT, as it does in GAT and NCT, and should be always taken into consideration.